JQuery UI 1.8, the User Interface Library for jQuery : build highly interactive web applications with ready-to-use widgets from the jQuery User Interface Library /: build highly interactive web applications with ready-to-use widgets from the jQuery User Interface Library. (2011) - Unknown
No abstract available